Impact of the childhood influenza vaccine programme on antibiotic prescribing rates in primary care in England. Issue 45 (29th October 2021) - Muller-Pebody, Berit; Sinnathamby, Mary A.; Warburton, Fiona; Rooney, Graeme; Andrews, Nick; Whitaker, Heather; Henderson, Katherine L.; Tsang, Camille; Hopkins, Susan; Pebody, Richard G.
Abstract: Vaccines are a key part of the global strategy to tackle antimicrobial resistance (AMR) since prevention of infection should reduce antibiotic use. England commenced national rollout of a live attenuated influenza vaccine (LAIV) programme for children aged 2–3 years together with a series of geographically discrete pilot areas for primary school age children in 2013 extending to older children in subsequent seasons. We investigated vaccine programme impact on community antibiotic prescribing rates. Antibiotic prescribing incidence rates for respiratory (RTI) and urinary tract infections (UTI; controls) were calculated at general practice (GP) level by age category (children<=10 years/adults) and season for LAIV pilot and non-pilot areas between 2013/14 and 2015/16. To estimate the LAIV (primary school age children only) intervention effect, a random effects model was fitted. A multivariable random-effects Poisson regression investigated the association of antibiotic prescribing rates in children with LAIV uptake (2–3-year-olds only) at GP practice level. RTI antibiotic prescribing rates for children <=10 years and adults showed clear seasonal trends and were lower in LAIV-pilot and non-pilot areas after the introduction of the LAIV programme in 2013. The reductions for RTI prescriptions (children) were similar (within 3%) in all areas, which coincided with the start the UK AMR strategy. Antibiotic prescribing was significantly (p < 0.0001) related to LAIV uptake in 2–3-year-olds with antibiotic prescribing reduced by 2.7% (95% CI: 2.1% to 3.4%) for every 10% increase in uptake. We found no evidence the LAIV programme for primary school age children resulted in reductions in RTI antibiotic prescribing, however we detected a significant inverse association between increased vaccine uptake in pre-school age children and antibiotic prescribing at GP level. The temporal association of reduced RTI and UTI antibiotic prescribing with the launch of the UK's AMR Strategy in 2013 highlights the importance of a multifaceted approach to tackle AMR.